PENGARUH DISIPLIN DAN MOTIVASI KERJA GURU TERHADAP KINERJA GURU SMP SE-KECAMATAN KEDUNGWUNI KABUPATEN PEKALONGAN - IDA WIJAYANTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Teacher performance is an important element in education which is a determinant of the high and low quality of educational outcomes. Factors that affect teacher performance are motivation and discipline, as has been proven by previous researchers. The aim of the research is to find out whether there is an effect of: (1) teacher work discipline on teacher performance; (2) teacher's work motivation on teacher performance; (3) discipline and teacher motivation on the performance of junior high school teachers in Kedungwuni District, Pekalongan Regency. The study population consisted of 175 junior high school teachers in Kedungwuni District, Pekalongan Regency with a sample of 122 people using the Proportionate Random Sampling technique. Data collection using the questionnaire method. Data analysis used descriptive analysis, prerequisite test and hypothesis testing of the regression analysis model with the help of the SPSS 25 for Windows program. The results of the hypothesis test found that discipline and work motivation simultaneously affect teacher performance by 20.5% and the remaining 79.5% from other variables not examined. The partial influence of work discipline on teacher performance is 4% and the influence of work motivation on teacher performance is 21.3%. The influence of work motivation dominates performance, so it is suggested that in improving teacher performance, schools must fulfill and increase their teacher's work motivation and can ignore work discipline. For future researchers to change the concept of data into work motivation as variable X1 and work discipline as variable X2 ABSTRAKKinerja guru elemen penting dalam pendidikan yang merupakan penentu tinggi rendahnya kualitas hasil pendidikan. Faktor yang mempengaruhi kinerja guru adalah motivasi dan kedisiplinan, sebagaimana telah dibuktikan peneliti sebelumnya. Tujuan penelitian untuk mengetahui apakah ada pengaruh: (1) disiplin kerja guru terhadap kinerja guru; (2) motivasi kerja guru terhadap kinerja guru; (3) disiplin dan motivasi kerja guru terhadap kinerja guru SMP se Kecamatan Kedungwuni Kabupaten Pekalongan. Populasi penelitian berjumlah 175 guru SMP se Kecamatan Kedungwuni Kabupaten Pekalongan dengan sampel 122 orang menggunakan teknik sampling Proportionate Random Sampling. Pengumpulan data menggunakan metode kuesioner. Analisis data menggunakan analisis deskriptif, uji prasyarat serta uji hipotesis model analisis regresi dengan bantuan program SPSS 25 for Windows. Hasil uji hipotesis ditemukan bahwa disiplin dan motivasi kerja secara simultan berpengaruh terhadap kinerja guru sebesar 20,5% dan sisanya 79,5% dari variabel lain yang tidak diteliti. Besarnya pengaruh secara parsial disiplin kerja terhadap kinerja guru 4% dan pengaruh motivasi kerja tehadap kinerja guru sebesar 21,3%. Pengaruh motivasi kerja lebih mendominasi terhadap kinerja, maka disarankan dalam meningkatkan kinerja guru, sekolah harus memenuhi serta meningkatkan motivasi kerja gurunya dan dapat mengabaikan disiplin kerja. Bagi peneliti selanjutnya agar mengubah konsep data menjadi motivasi kerja sebagai variabel X1 dan disiplin kerja sebagai variabel X2